Image and recognition of illustrious nurses through world coins - Juan Francisco Reyes Revuelta (Universidad de Alicante, 2018)
Over the last few years there has been a growing interest in iconography as an instrument for the historical research of the Nursing profession. There are still few and little known articles which use Numismatics as a source of study for the construction of the History of Care and Nursing. The present study aims, using a descriptive and documentary observation methodology, to locate and identify world coins in which are appreciated work and contributions to the profession and the society of illustrious nurses. A total of eleven coins considered relevant for the present study were selected. A small biographical account of the nurse that appears in each coin is made and coin description is made applying iconographic methodology. It is necessary to continue identifying, describing and contextualizing numismatic issues of interest for the study of the History of Care and Nursing.